Development and validation of measuring instruments of contextualization of science among Malaysian and Nigerian serving and pre-service chemistry teachers - Oloruntegbe, K.O.; Zamri, S.N.A.S.; Saat, R.M.; Alam, G.M. (Academic Journals, 2010)
The purpose of this study is to develop and validate instrument for assessing Malaysian and Nigerian serving and pre-service chemistry teachers' contextualization of science knowledge, skills and attitudes and their application outside classroom. Forty item test and twenty item inventory were initially developed. A panel of experts was used for content validity. Readability of the instrument was determined using a sample of 25. Data on pilot study were collected from administration of the instrument on further 85 subjects. The data were used to determine internal consistency and reliability of the instruments. Twenty five items of the test and the entire ones of the inventory were left after these determinations. The results indicated that the instrument possesses high internal consistency and coefficient values, and that it is adjudged significantly suitable for the purpose and other researchers would find the instrument very useful.